VD_FINDINFO Jug / 2011 / 288 vom 11. Juli 2011 - VD Tribunal cantonal (2011)
CONSTATATION DES FAITS, FIXATION DE LA PEINE, ATTÉNUATION DE LA PEINE, EFFET, PEINE, AUTEURDROIT PÉNAL | 47 CP, 54 CP, 70 al. 1 CP, 398 al. 3 let. a CPP (CH), 428 al. 2 let. b CPP (CH)